The pattern of state organization in the new constitution of Lithuania: A third way between the presidential and parliamentary systems? - Hollstein, Andreas (Politologija, 1999)
In this article, Andreas Hollstein refers to the Constitution of the Republic of Lithuania and, by that token, discusses the pattern of state power structure as established by it. The author focuses the analysis upon the following question: does the Constitution of the Republic of Lithuania of 1992 establish a third way between the parliamentary and presidential democracy?In this article, he first questions and, later, recognizes that such a way is but void and that the Constitution of the Republic of Lithuania should be interpreted as parliamentary, enriched with some attributes of the presidential system. Andreas Hollstein writes: "Constitutional patterns of state organization and governmental systems have come to the heart of international concern, provided that on the basis of the pattern of state organization the conclusions both regarding the political stability of the country and the predictability of its behavior inside the international community of states may be inferred."Throughout the article, the author oftentimes refers to a widely discussed ruling of the Constitutional Court of Lithuania dated January 10, 1998, regarding the compatibility of the program of the Government of Lithuania with the Constitution of Lithuania. The author, while retaining the contact with this ruling and at the same time meeting the aim of the study—that is, to classify the structural pattern of state as noted in the Constitution, 1992—acknowledges: "provided that in this ruling the attention was drawn upon the question whether or not the resolution adopted by Seimas' majority on December 11, 1996, questioning the compatibility of the program of the Government of the Republic of Lithuania with the Constitution of Lithuania, the Constitutional Court ought to have turned its inquiry in such a way so that the background power balance of Lithuania’s state institutions be analyzed in detail.In my opinion, this ruling has in details missolved the question of governmental authority and contributed but little to a systemic explanation (zur systematischen Einordnung) of the pattern of the Lithuania state power structure." On the same page, having ascertained that "the ruling of the Constitutional Court has revealed clearly that the power system of Lithuania's authority still requires fundamental explanation and classification," the author, at once, adds actuality and practical significance to the effort of his own.While trying to answer the proposed question—that is, does the Constitution of the Republic of Lithuania of 1992 establish a third way between the parliamentary and presidential democracy?—the author employs the work-writing manner which is characteristic to analytical work and which consists of the following parts: theoretical part, descriptive part, and evaluative-analytical part.The first part, thus, is theoretical. Herein the reader is introduced to three theoretical patterns for systematization of the state organization used in the legal theory of state and meant to identify the parliamentary and presidential systems: bipolar systematization, systematization based upon the concrete patterns of the phenomena, and semi-presidentialism as a third way of systemizing the governments.While construing this part, the author provides to use the theoretical patterns and practical considerations of almost ten political thinkers and scientists, less-known authors like Steffani, Schmitt, Beyme, Loewenstein, Kaltefleiter, Brunner, and classics like Duverger, Sartori, Lijphart.It is the introduction where Andreas Hollstein, citing Haberle, notes that in the process of applying the legal sciences of state to the analysis of the European states' constitutional development, trends of constitutional internationalization and assimilation are to be discovered. In the legal doctrine of the modern state, these trends are titled by using the concept of "co-European constitutional law."However, the author, while noting the visual difficulties that were encountered by Western scientists while applying classical and usual patterns of constitutional state organization in the analysis of new East-Central European constitutions, notes that "the patterns of the evolving European constitutions, especially the constitutional patterns of state organization in young Central-East European states, are diverse and scattered ... which gives trouble to all attempts to systemize the patterns of these phenomena, both the constitutions and authority systems" and so to contribute to further classification and comparison of the latter.In the theoretical section, he writes that the classification of the patterns of state organization is relatively simple in the cases when the characteristics of the classified system correspond to the essential features of either British or American systems.However, in spite of the strong co-European trend, wide similarity between the state organizations still seems to be an exception. In reality, the gap between the systems is broad and complicated. Thus, to retain the option for classification, the scientists—in addition to the dominant designation between parliamentary and presidential regimes—have developed diverse additive models.At this point, the ever-changing combinations of the corresponding elements in these additive models burden the attempts of classifying new constitutions of East-Central European states and raise an even more important question: does some specific feature characteristic to the state and explained by the political peculiarities of its life serve as a sufficient ground to identify as a semi-presidential not only this system, but all the other systems as well, to whatever extent they are detached from the latter?Therefore, there appears a question: is there a semi-presidential system with itemized features at all? Besides, only on rare occasions is it clear whether the author strives to distance himself from an alternative standpoint—that is, whether he speaks of the authoritative system sui generis—or limits himself to describing one of the subgroups of the parliamentary power structure.According to Andreas Hollstein, "unfortunately, but the same is said about the ruling of the Constitutional Court of Lithuania, dated January 1998."The second section of the study is descriptive. Save looking at the pattern of state organization established in the Constitution of Lithuania, the author describes and to some smaller extent assesses the competence of separate institutions of the Lithuania-State, namely, Seimas, the President, and the Government.He documents the political events of the last nine years in Lithuania and, by that token, determines the relationship between the President and Seimas, the President, Seimas, and the Government. The author goes beyond the description of the last-decade constitutional relationship of these institutions, oftentimes embracing comparisons with the Constitutions of Lithuania, as of 1922 and 1938.Interesting conclusions are made. When it regards the present period, the author elevates as the most important the relations between the President and Seimas, apportioning these into three periods: from 1993 up to 1996, from 1996 until the end of 1997 and the election of Valdas Adamkus, and the present, the ongoing period.Having presented the collection of the constitutional powers of the President—"direct foreign policy competence, authority to dissolve the parliament, the power to initiate legislation, the suspensive veto right, and versatile opportunities to influence the personal structure of the Government"—the author, likewise, notes that the Presidential powers, especially when confronted by Seimas' powers, are limited.In his words, the core instrument of the Head of State in order to influence the decisions is the public opinion and direct elections. Another essential conclusion—namely, that the pressure Seimas exceeds on the President seems stronger than if vice versa.The author notifies that according to the Constitution the weakest institution is the Government and accentuates the aspect of double accountability (both to the President and Seimas). However, even in this case, in case of controlling the Government, Seimas has the constitutional advantage.Later, the author proceeds to the third section of the work—classification of the pattern of state organization as established in the Constitution of Lithuania, 1992.In the conclusion of this part, the author, save employing the theoretical patterns and methods of systemizing the state regime he has first provided in the theoretical section of the work, still tries to answer the question of the work: does the Constitution of the Republic of Lithuania, 1992 establish a third way between the parliamentary and presidential democracy?If not—how could such a structure be classified? The author compares the data he has arranged in the second part with the premises of theoretical patterns. The conclusion is inferred—the third way is but void and that the Constitution of the Republic of Lithuania should be interpreted as parliamentary, accompanied by some attributes of the presidential system.In conclusion, it can be said that in this article the author has managed to construe firm theoretical background, which, reinforced by various theoretical premises inscribed in theoretical patterns and conclusions of various political scientists and elegant informativeness (which is revealed in the second part) of the author, contributes to a constructive evaluation of the pattern of Lithuania-State organization and serves as a ground to further discussions in the field.
Keywords: -